Australicola pectinatus n. gen. and n. sp. (Cestoda: Pseudophyllidea) from the deep-sea fish Beryx splendens from Tasmania - Kuchta, Roman; Scholz, Tomás (The Journal of parasitology, 2006)
Australicola pectinatus n. gen., n. sp. (Pseudophyllidea: Triaenophoridae) is proposed to accommodate a new cestode from a deep-sea fish, the splendid alfonsino, Beryx splendens Lowe, 1834 (Beryciformes: Berycidae), from the Pacific coast of Tasmania. The new genus is placed in the Triaenophoridae, because it possesses a ventral uterine pore, marginal genital pore, and follicular vitellarium. Australicola is characterized by possessing a massive strobila with very short and wide, markedly craspedote proglottids; vitelline follicles forming a transverse equatorial band; a very deep and narrow genital atrium; a wide, convoluted vaginal canal; and unoperculate eggs. Australicola most closely resembles Eubothrium Nybelin, 1922 and Probothriocephalus Campbell, 1979 in having an unarmed scolex, an unarmed cirrus, the vagina anterior to the cirrus-sac, and cortical vitellaria. It differs from these 2 genera, in addition to the characteristics listed above, in possessing a dendritic rather than an entire ovary. Australicola pectinatus n. sp. is the third cestode described from B. splendens.
Keywords: Fish Diseases; nemoci ryb; střeva; oceány a moře; ryby; Tasmánie; cestodózy; Intestines; Cestoda; druhová specificita; Species Specificity; Cestode Infections; Tasmania; Oceans and Seas; Animals; Fishes; zvířata